Clinician Perspectives Regarding In-Hospital Cardiac Arrest Resuscitation: A Multicenter Survey. Issue 3 (March 2019) - Peltan, Ithan D.; Poll, Justin; Sorensen, Jeffrey; Guidry, David; Chandler, Marni; Beninati, William; Brown, Samuel M.
Abstract : Objectives: Evaluate clinicians' sentiments about participating in cardiac arrest resuscitations and identify factors associated with confidence in resuscitation of cardiac arrest. Design: Electronic survey. Setting: Twenty-one hospitals in Utah and Idaho. Subjects: All attending physicians, residents, and nurses in a multilevel healthcare system likely to participate in an in-hospital cardiac arrest resuscitation at least once every 2 years. Interventions: None. Measurements and Methods: A survey instrument evaluating clinician perceptions of in-hospital cardiac arrest resuscitation participation was developed after literature review and iteratively revised based on expert input and cognitive pretesting. Survey responses were collected anonymously. Sixty percent of 1, 642 contacted clinicians ( n = 977) submitted complete responses, of whom 874 met study inclusion criteria (190 attending physicians, 576 nurses, and 110 residents). Most respondents (74%) participated in less than or equal to six in-hospital cardiac arrest events per year, and 41% of respondents were most likely to participate in in-hospital cardiac arrest resuscitation at a community, rural, or critical access hospital. Confidence in in-hospital cardiac arrest participation was high overall (92%), but lower among residents (86%) than nurses (91%) or attending physicians (96%; p = 0.008). Fewer residents (52%) than nurses (73%) or attending physicians (95%; p < 0.001) reported feeling confident leading in-hospital cardiac arrest teams. Residents (63%) and attending physicians (36%) were more likely to worry about making errors during an in-hospital cardiac arrest event than nurses (18%; p < 0.001). Only 15% of residents and 50% of respondents overall reported they were both confident participating in in-hospital cardiac arrest resuscitation and did not worry about making errors. In-hospital cardiac arrest participation frequency was the dominant predictor of respondents' confidence leading or participating in an in-hospital cardiac arrest resuscitation. Conclusions: Many clinicians, especially residents, who participate in or lead in-hospital cardiac arrest resuscitation events lack confidence or worry about management errors. Hospitals—particularly smaller hospitals—should consider methods to provide in-hospital cardiac arrest teams additional "effective experience, " potentially using simulation or telemedicine consultation. Abstract : Supplemental Digital Content is available in the text.